2004
DOI: 10.1023/b:nere.0000010447.24128.ac
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phospholemman Expression on Swelling-Activated Ion Currents and Volume Regulation in Embryonic Kidney Cells

Abstract: Phospholemman (PLM) is a 72-amino-acid phosphoprotein that is a major substrate for cAMP-dependent protein kinase, protein kinase C, and NIMA kinase. In lipid bilayers, PLM forms ion channels selective for Cl-, K+, and taurine. Effluxes of these abundant intracellular osmolytes play an important role in the control of dynamic cell volume changes in many cell types. We measured swelling-activated ion currents and regulatory volume decrease (RVD) in human embryonic kidney cells stably overexpressing canine cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 57 publications
2
28
0
Order By: Relevance
“…1D). In agreement with previous studies, neither NCX1 (8) nor PLM (19) was detected in HEK293 cells transfected with only the empty pAdTrack expression plasmid (image not shown; Western blots shown in Fig. 2).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1D). In agreement with previous studies, neither NCX1 (8) nor PLM (19) was detected in HEK293 cells transfected with only the empty pAdTrack expression plasmid (image not shown; Western blots shown in Fig. 2).…”
Section: Resultssupporting
confidence: 93%
“…pcDNA3-expressing PLM also demonstrated the minor bands (19). The identities of these minor bands are at present unknown.…”
Section: Inhibition Of Na ϩ /Ca 2ϩ Exchanger By Phospholemmanmentioning
confidence: 93%
“…There are strong interactions between various residues occluding the central pore of the tetramer; thus, we believe that any conformational change to an open pore would require major structural rearrangements and disruption of interresidue interactions, which are incompatible with the typical delicate balance between open-close conformations in voltage-or ligand-gated transmembrane channels. However, it has been shown that hyperpolarization activates anion currents through PLM (40), and based on further experiments with embryonic kidney cells, it has been hypothesized that PLM may facilitate osmolyte influx in renal tissue (18). Indeed, the clustering of four negative charges at the extracellular entrance would provide a binding site for the zwitterionic osmolyte taurine.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical measurements of PLM in artificial lipid bilayers and oocytes showed that PLM facilitates the membrane flux of ions (16) and taurine transport (17), which leads to the possibility that PLM has a function in the regulation of cell volume either as a modulator of a swelling-activated signal transduction pathway or directly facilitating osmolyte influx in noncardiac tissues (18).…”
Section: Human Phospholemman (Plm)mentioning
confidence: 99%
See 1 more Smart Citation